Comprehensive insights into the multifaceted roles of the transient receptor potential vanilloid 1 channel in the digestive system - Wang, Juan; Kumar, Pavitra; Engelmann, Cornelius (Life sciences (1973), 2023)
The transient receptor potential vanilloid (TRPV) channel, a family of calcium transporters comprising six distinct members (TRPV1–6), takes on a paramount role in maintaining intracellular Ca2+ homeostasis in mammalian cells. Notably, TRPV1, among its counterparts, has emerged as the subject of extensive scrutiny, owing to its pervasive presence in diverse cellular, tissue, and organ settings. This ubiquitous distribution underscores its fundamental involvement in the genesis of pain, making it a central focus in pain-related research. However, recent investigations have unveiled that TRPV1's functional significance transcends the realm of pain modulation, extending its influence to encompass a wide spectrum of physiological and pathological processes. The ambit of TRPV1's influence encompasses not only pain responses but also embraces the intricate domains of nervous system disorders, cancer metastasis, as well as afflictions pertaining to the skin and heart. Moreover, compelling evidence now demonstrates that TRPV1 also wields substantial sway in the domain of digestive diseases, further highlighting its versatility and far-reaching impact on human health. Therefore, this comprehensive review endeavors to delve into the multifaceted roles played by TRPV1 in the various organs constituting the digestive system. [Display omitted]